PENGARUH STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2014 - Nuraini Nuraini; Makhdalena Makhdalena; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to investigate the effect of Managerial Ownership, Institutional Ownership and Public Ownership of the Capital Structure. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange that has the necessary data (managerial ownership, institutional ownership and possession of the governments) 6 consecutive years - succession (2008-2014). The data used is secondary data. Data analysis technique using multiple regression analysis. The result showed that the Managerial Ownership, Institutional Ownership and Public Ownership simultaneously affect the capital structure of 0.851. Further research showed partial effect on the Managerial Ownership Capital Structure of 0.140625. Institutional ownership affect the capital structure of 0.031684. Public ownership affect the capital structure of 0.083521. Keywords: Managerial Ownership, Institutional Ownership, Public Ownership and Capital Structure